Market Size in Innovation: Theory and Evidence from the Pharmaceutical Industry - Acemoglu, D.; Linn, J. (Quarterly Journal of Economics, 2004)
This paper investigates the effect of (potential) market size on entry of new drugs and pharmaceutical innovation. Focusing on exogenous changes driven by U. S. demographic trends, we find a large effect of potential market size on the entry of nongeneric drugs and new molecular entities. These effects are generally robust to controlling for a variety of supply-side factors and changes in the technology of pharmaceutical research.